Chitosan and Its Nanoparticles: A Multifaceted Approach to Antibacterial Applications - Emir Akdaşçi; Hatice Duman; Furkan Eker; Mikhael Bechelany; Sercan Karav (Nanomaterials)
Chitosan, a multifaceted amino polysaccharide biopolymer derived from chitin, has extensive antibacterial efficacy against diverse pathogenic microorganisms, including both Gram-negative and Gram-positive bacteria, in addition to fungi. Over the course of the last several decades, chitosan nanoparticles (NPs), which are polymeric and bio-based, have garnered a great deal of interest as efficient antibacterial agents. This is mostly due to the fact that they are used in a wide variety of applications, including medical treatments, food, chemicals, and agricultural products. Within the context of the antibacterial mechanism of chitosan and chitosan NPs, we present a review that provides an overview of the synthesis methods, including novel procedures, and compiles the applications that have been developed in the field of biomedicine. These applications include wound healing, drug delivery, dental treatment, water purification, agriculture, and food preservation. In addition to this, we focus on the mechanisms of action and the factors that determine the antibacterial activity of chitosan and its derivatives. In conjunction with this line of inquiry, researchers are strongly urged to concentrate their efforts on developing novel and ground-breaking applications of chitosan NPs.